PENGARUH EARLY WARNING SYSTEM TERHADAP PROFITABILITAS DENGAN COMPANY SIZE SEBAGAI MEDIASI PADA ASURANSI SYARIAH INDONESIA - Kurniati, Putri Ayushifa; Wibisono, Masodah (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the effect of the early warning system, measured by the claim burden ratio, fund adequacy ratio, premium growth ratio, and self-retention ratio, on profitability (ROE) with Company size as a mediating variable. The analysis method used in this study employs quantitative secondary data in the form of panel data obtained from the financial reports of Islamic insurance companies registered as members of the Indonesian Islamic Insurance Association (AASI) and supervised by the Financial Services Authority (OJK). The sample in this study was determined using purposive sampling techniques and resulted in the number of Islamic insurance companies that met the research criteria. The testing tool used was Eviews 12. The results of the study indicate that the claim expense ratio and premium growth ratio do not affect profitability or Company Size. The capital adequacy ratio has a significant negative effect on both, while the retention ratio has a significant positive effect. Additionally, Company size has a negative effect on profitability and only mediates the relationship between the capital adequacy ratio and profitability.